Teplizumab: A Disease-Modifying Therapy for Type 1 Diabetes That Preserves β-Cell Function - Herold, Kevan C.; Gitelman, Stephen E.; Gottlieb, Peter A.; Knecht, Laura A.; Raymond, Ralph; Ramos, Eleanor L. (Diabetes care, 2023)
In November 2022, teplizumab-mzwv became the first drug approved to delay the onset of stage 3 type 1 diabetes in adults and children age ≥8 years with stage 2 type 1 diabetes on the basis of data from the pivotal study TN-10. To provide confirmatory evidence of the effects of teplizumab on preserving endogenous insulin production, an integrated analysis of C-peptide data from 609 patients (n = 375 patients receiving teplizumab and n = 234 control patients) from five clinical trials in stage 3 type 1 diabetes was conducted. The primary outcome of the integrated analysis, change from baseline in stimulated C-peptide, was significantly improved at years 1 (average increase 0.08 nmol/L; P < 0.0001) and 2 (average increase 0.12 nmol/L; P < 0.0001) after one or two courses of teplizumab. An analysis of exogenous insulin use was also conducted, showing overall reductions of 0.08 (P = 0.0001) and 0.10 units/kg/day (P < 0.0001) at years 1 and 2, respectively. An integrated safety analysis of five clinical trials that enrolled 1,018 patients with stage 2 or 3 type 1 diabetes (∼1,500 patient-years of follow-up for teplizumab-treated patients) was conducted. These data confirm consistency in the preservation of β-cell function, as measured by C-peptide, across multiple clinical trials. This analysis showed that the most common adverse events included lymphopenia, rash, and headache, a majority of which occurred during and after the first few weeks of teplizumab administration and generally resolved without intervention, consistent with a safety profile characterized by self-limited adverse events after one or two courses of teplizumab treatment.